EFEK STRENGTHENING DAN PROPRIOCEPTIVE TRAINING TERHADAP PENURUNAN INTENSITAS NYERI DAN PENINGKATAN KEMAMPUAN FUNGSIONAL PASIEN SPRAIN ANKLE : Literature Review - Indiana Radinda, (2020)
Background : Sprain ankle is a condition where ankle's ligament overstretched because of the trauma that cause injury in lateral ankle's ligament and sometimes with tendon's injury. This literature study aims to reviewing some literatures about the intervension of Strengthening and Proprioceptive Training for decreasing pain intensity and increasing functional ability in people with Grade I sprain ankle. Method : This study literatur design use systematic review method which aim to identify all available literature about a case to make sure that no information has missed about pain and functional ability in sprain ankle and intervention that contains Strengthening and Proprioceptive Training with inclusion criteria individual with Grade I sprain ankle, feel pain in injury area, age range 16-45 years old, and follow all the program that given. Result : Six literatures fill all the inclusion criteria with score 6/10 - 9/10 based on PEDro Scale. Conclusion : The intervention of Strengthening and Proprioceptive Training can reduce pain intensity and increase functional ability in patients with Grade I sprain ankle. Keyword : Grade I Sprain Ankle, Pain, Functional Ability, Strengthening, Proprioceptive Training